Preparation of electrospun polyvinylidene fluoride/nanosilver nanofibrous membrane and its antimicrobial potential / Norasikin Ahmad - Norashikin , Ahmad (2018)
In the current study, nanofibrous membrane (NFM) was produced through electrospinning and developed as a cost-effective membrane that able to improve the microbial quality of water, by removing Escherichia coli (E. coli), which is a type of fecal coliform bacteria, as well as fecal contamination indicator from the raw water. Electrospun NFM was prepared by incorporating as-synthesized nanosilver particles (NSPs) into polyvinylidene fluoride (PVDF). In phase I, an investigation was performed to obtain the smallest size of NSPs by varying precursor concentration (0.1 M, 0.5 M and 1.0 M) and reaction temperature (60 °C and 80 °C). At 60 °C, the size was increased as the precursor concentration increased from 0.1 M to 0.5 M. When the concentration further increased to 1.0 M, the size becomes smaller due to the fewer Ag+ released upon the incomplete precursor reduction by the reducing agent. In contrast, at 80 °C, the size was gradually increased as the precursor concentration increases up to 1.0 M. In terms of controlled precursor concentration, the physical size and crystallite size become smaller as the temperature increases. In general, the hydrodynamic, physical and crystallite size of NSPs displayed similar trends. In this phase, S1T8 which have the smallest physical size and crystallite size was chosen to proceed to the next phase. The second phase was carried out to investigate the properties of electrospun PVDF/NSPs NFM. The morphological study revealed that the electrospun NFM form randomly oriented fibers, fewer beads as well as increasing average fiber diameter up to 311.2 nm when NSPs load increases from 0.5 wt% to 3.0 wt%. Through the elemental and microstructural study by energy dispersive spectrometer (EDS) and X-ray diffractometer (XRD), NSPs were detected in each membrane that verifies NSPs successfully incorporated into the membrane. The XRD diffraction pattern exhibited that the PVDF crystalline phases kept constant after the incorporation of different NSPs loads, while, the NSPs crystallinity slightly changed which might due to the crystallite growth or increment of crystallinity degree. In nitrogen physisorption analysis, the electrospun NFM displayed type IV isotherm that proves they are the mesoporous membrane and has pore size range from 4.16 to 34.93 nm, which able to retain the bacteria cells from passing through the membrane. The last phase was related to the efficacy of electrospun NFM in removing E. coli. As a model of contaminated water, E. coli with standardized concentration was spiked into the sterile saline water and then was passed through the sterile electrospun NFM. The removal efficiency of the E. coli was determined by colony counts on the membrane. The colony counting results showed that the concentration of E.coli decreased as the NSPs loading increased. The highest E. coli removal effectiveness was achieved by a membrane that contains 3.0 wt% of NSPs. Leaching analysis by UV-vis spectrophotometer exposed the absence of the silver element in the filtrate which proves NSPs did not leach from the membrane. Overall, the electrospun PVDF/NSPs NFM capable to generate clean water, which is free from pathogens and also silver.